Hypothalamic-pituitary-adrenal axis activity and its relationship to the autonomic nervous system in patients with psychogenic erectile dysfunction - Xu, Jinzhou; Chen, Yinwei; Gu, Longjie; Liu, Xiaming; Yang, Jun; Li, Mingchao; Rao, Ke; Dong, Xiyuan; Yang, Shulin; Huang, Bo; Jin, Lei; Wang, Tao; et al. (Frontiers in Endocrinology, 2023)
Background: Psychological stress and its two stress response systems, the hypothalamic-pituitary-adrenal (HPA) axis and the autonomic nervous system (ANS), are closely related to psychogenic erectile dysfunction (pED). However, the analyses of perceived stress and stress systems in pED patients have not been in-depth enough, especially the interactions between them. Methods: Our study included 75 patients with pED and 75 healthy men. The International Index of Erectile Function-5 (IIEF-5) and the 10-item Perceived Stress Scale (PSS-10) were used for assessing the severity of ED and perceived Stress. All participants collected saliva samples on 3 consecutive days at 8 specific times with strict reference to time of morning awakening for measuring cortisol parameters, and wore an electrocardiography for 24 h to derive heart rate variability (HRV). Results: The PSS-10 scores of pED patients were significantly higher than the control group (p<0.001). Although PSS-10 and IIEF-5 scores were negatively correlated in pED patients, there was no statistical significance between them (r=−0.049，p=0.677). Compared with the control group, the HRV parameters of pED patients were significantly increased in LF/HF ratio (p=0.014), but significantly decreased in LF, HF and pNN50 (p<0.001). However, there were no statistically significant differences in any of the cortisol variables between the two groups (all p>0.05). The interaction between sympathovagal modulation (HF, rMSSD) and cortisol awakening response (CAR AUCi) explained significantly greater variance in perceived stress than either stress system alone. Higher parasympathetic activity combined with higher cortisol awakening response was associated with greater perceived stress. Conclusion: Our results suggested that the inter-relation between ANS and HPA axis activity might enhance our comprehension of how stress affected the physical and mental health of pED patients.